Operational Risk Analysis and Prioritization of Mitigation Strategies in the Production Process of Processed Sweet Potato Products at Ummah Cookies - Anita, Anita; Rakhmawati, Ismi Yayuk Rakhmawati (UNIPA PRESS, 2026)
The development of the local food industry in Indonesia faces challenges due to the increasing dominance of modern and imported food products, which have caused local food-based processed products to be increasingly marginalized. Ummah Cookies, as a local food processing MSME based on sweet potatoes and cassava, still faces various operational risks that have the potential to affect product quality and the stability of the production process. This study aims to analyze operational risks and determine risk mitigation strategies in the production process of sweet potato processed products at Ummah Cookies. The method used in this study is a combination of Failure Mode and Effects Analysis (FMEA) and Analytical Hierarchy Process (AHP). The FMEA method is used to identify and prioritize risks based on Severity, Occurrence, and Detection values ​​through the calculation of the Risk Priority Number (RPN), while the AHP method is used to determine the priority of risk mitigation strategies. The results of the study showed that the highest risk in sweet potato brownies products was at the production stage in the form of the emergence of a strong sweet potato aroma with an RPN value of 330. Meanwhile, in sweet potato porridge products the highest risk was at the post-production stage in the form of products that spoil quickly during storage with an RPN value of 342. The results of the AHP analysis showed that the priority of risk mitigation in sweet potato brownies lies in the production aspect with an eigenvector value of 0.61, while in sweet potato porridge it lies in the post-production aspect with an eigenvector value of 0.49. Recommended risk mitigation strategies include controlling the quality of raw materials, controlling the temperature and cooking process, implementing production SOPs, and optimizing product storage and packaging systems. The implementation of these strategies is expected to be able to maintain product quality stability, increase production process efficiency, and minimize potential losses in local food MSMEs.